The Role of MMP2 (-1306C>T) and TIMP2 (-418 G>C) Promoter Variants in Age-related Macular Degeneration. (28th March 2013) - Ortak, Huseyin; Demir, Selim; Ateş, Ömer; Benli, İsmail and Söğüt, Erkan and Sahin, Mehmet
Abstract: Purpose : To investigate the possible association between the matrix metalloproteinase 2 ( -1306C>T ) (rs 243865) and tissue inhibitors of matrix metalloproteinase 2 (- 418 G>C ) (rs 8179090) polymorphisms and the risk of age-related macular degeneration. Methods : This case-controlled prospective study included 144 age-related macular degeneration patients and 172 control subjects. All subjects were screened for age, gender, hypertension (HT), diabetes (DM), and body mass index (BMI). Serum levels of high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), total cholesterol (TC), and smoking were also determined. Genomic DNA was extracted from peripheral leukocytes from ethylenediaminetetraacetic acid anticoagulated blood. Genotyping of the MMP2 ( -1306C>T ) and TIMP2 (- 418 G>C ) polymorphisms was performed using real-time polymerase chain reaction. Results : Genotype distributions or allelic frequencies of MMP2 ( -1306C>T ) and TIMP2 (- 418 G>C ) did not significantly differ between patients with AMD and control subjects. Similarly, no significant differences in either genotype distributions or allelic frequencies of MMP2 ( -1306C>T ) and TIMP2 (- 418 G>C ) were found between dry and wet AMD. Conclusion : MMP2 ( -1306C>T ) and TIMP2 ( -418 G>C ) promoter variants are unlikely to have a major role in age-related macular degeneration risk susceptibility.